DIAGRAMAS BINARIOS SÓLIDO-LÍQUIDO MOSTRANDO LA FORMACIÓN DE COMPUESTOS EN UNA MEZCLA DE SOLVENTES POLARES (2003)
Binary liquid-solid diagram compound formation in mixtures of carbon tetrachloride-dioxane and dioxinchloroform with metastable melting-points is shown. A compound formation is observed in the mixture carbon tetra chloride-dioxane at 33 mol % dioxane. The results are analyzed and compared with literature data. This experiment introduces the student to handle low temperatures in a simple experiment set up.